2005
DOI: 10.1111/j.1600-6143.2005.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response Against the Glomerular Basement Membrane Protein Agrin in Patients with Transplant Glomerulopathy

Abstract: Chronic allograft nephropathy (CAN) of renal allografts is still the most important cause of graft loss. A subset of these patients have transplant glomerulopathy (TGP), characterized by glomerular basement membrane (GBM) duplications, but of unknown etiology. Recently, a role for the immune system in the pathogenesis of TGP has been suggested. In 11 of 16 patients with TGP and in 3 of 16 controls with CAN in the absence of TGP we demonstrate circulating antibodies reactive with GBM isolates. The presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 41 publications
1
97
1
Order By: Relevance
“…Urine proteomic analysis identified LG3 as a novel biomarker of CTV in renal transplant recipients [30,31,58]. The present work demonstrates that LG3 could participate in the pathophysiology of CTV through inhibition of apoptotic pathways in hMSC.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Urine proteomic analysis identified LG3 as a novel biomarker of CTV in renal transplant recipients [30,31,58]. The present work demonstrates that LG3 could participate in the pathophysiology of CTV through inhibition of apoptotic pathways in hMSC.…”
Section: Discussionmentioning
confidence: 77%
“…Endothelial apoptosis triggers the extracellular export of cathepsin L and other proteases, thereby inducing basement membrane proteolysis, a characteristic feature of CTV [3,30,31]. In turn, proteolysis of basement membrane perlecan leads to the production of an antiapoptotic carboxyl-terminal (C-terminal) fragment active on vascular smooth muscle cells and fibroblasts [29,32].…”
Section: Introductionmentioning
confidence: 99%
“…A recent intriguing study also revealed antibodies targeting angiotensin II type 1 receptor in kidney transplant recipients with "vascular rejection," who did not have detectable DS anti-HLA antibodies (36). Joosten et al (37) demonstrated antibodies to glomerular basement membrane-heparan sulfate proteoglycan agrin in the sera of patients with transplantation glomerulopathy, a sign of chronic allograft rejection. Although these data point toward a potential role for non-HLA antidonor antibodies in allograft rejection, more work will be needed to analyze whether these non-HLA antibodies are secondary to immune-mediated allograft injury or have a primary role as well.…”
Section: Type Of Antibody and Its Effect On Allograft Outcomementioning
confidence: 99%
“…One example of this phenomenon in humans is the development of de novo posttransplant antibodies and T cell reactivity to lung-expressed type V collagen in lung transplant patients with bronchiolitis obliterans. 8 Other associations include anti-angiotensin II receptors 9 or anti-agrin 22 antibodies in patients with kidney transplant rejection.…”
mentioning
confidence: 99%